FEYNMAN INTEGRALS PERTAINING TO ALEPH FUNCTION AND TWO GENERAL CLASS OF POLYNOMIALS - Shekhawat, Ashok Singh; SHARMA, SUNIL KUMAR (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The object of the present paper is to derive certain integral properties of Aleph function and two general class of polynomials. During the course of finding, we obtain some particular cases, which are also new and of interest by themselves. The N-function is a generalization of the familiar H-function and the I-function. The results derived are of general character.